Islamic view of gluttony explained from medical and scientific point of view - Majid, Mohammed Abdul (Journal of Islam and Science, 2023)
From the time of the Prophet SAW and his companions till today, during these fifteen centuries, the muslim ummah has undergone a profound change in its lifestyle, including the food habits. From highly simplistic and frugal way of life to a highly opulent and extravagant living. This, in turn, in addition to causing various health issues, is also making it difficult for the ummah to discern the huge benefits of following the Sunnah of the Prophet SAW in their daily life. For example, a health issue of gluttony which was unheard of during the time of the Prophet SAW, is becoming common in the ummah. Take for example, the use of sifter, which has become a thing of common use in our daily lives, was in seldom use during the time of the Prophet SAW. In this paper we have strived to bring home the critical lesson for the ummah to obediently follow the practices of the Prophet SAW and his Sahaba RA in their daily lives. Qur’an and Hadith are replete on this valuable subject. And now science after fifteen centuries has come to the conclusion that what was said in Qur’an and Hadith are coming true in letter and spirit.